Effectiveness Of Preoperative Antibiotic Prophylaxis Timing in Reducing Surgical Site Infections: A Prospective Observational Study - R Navalyal, Sanjeev; Kumar K H, Praveen; Hoogar, Prafullachandra; Mankani, Lata K (Journal of Neonatal Surgery, 2025)
Background: Surgical site infections (SSIs) remain a significant cause of postoperative morbidity, increased healthcare costs, and prolonged hospital stays despite advances in surgical techniques and antimicrobial therapy. The timing of preoperative antibiotic prophylaxis administration has been identified as a critical factor in SSI prevention, yet optimal timing parameters remain debated. This study aimed to evaluate the effectiveness of different preoperative antibiotic prophylaxis timing intervals in reducing SSIs across various surgical procedures. Methods: A prospective observational study was conducted at a tertiary care teaching hospital from January 2023 to December 2023. We enrolled 450 patients undergoing clean and clean-contaminated surgeries who received prophylactic antibiotics. Patients were categorized into three groups based on antibiotic administration timing: Group A (120-60 minutes before incision), Group B (60-30 minutes before incision), and Group C (30-0 minutes before incision). Patient demographics, comorbidities, surgical characteristics, timing of antibiotic administration, and development of SSI within 30 days post-surgery were recorded. Statistical analysis was performed using chi-square tests and multivariate logistic regression to identify significant associations. Results: The overall SSI rate was 7.6% (34/450 patients). SSI rates by timing group were: Group A (120-60 minutes) 12.1%, Group B (60-30 minutes) 4.2%, and Group C (30-0 minutes) 6.8%. Multivariate analysis revealed that antibiotic administration 60-30 minutes before incision was associated with significantly lower SSI rates compared to other timing intervals (adjusted OR 0.38, 95% CI 0.21-0.67, p=0.001). Additional independent risk factors for SSI included diabetes mellitus, prolonged operative time (>2 hours), emergency surgeries, and higher ASA scores. Conclusion: This study demonstrates that optimal timing of preoperative antibiotic prophylaxis is 60-30 minutes before surgical incision. Implementation of standardized protocols emphasizing this timing window could significantly reduce SSI rates. Hospital antimicrobial stewardship programs should focus on this timing parameter as a key quality improvement measure